YOGA: THE TRANSFORMATIVE POWER OF SPORT (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article examines the transformative impact of yoga on human life from a sports perspective. The importance of yoga in improving physical and mental health, its role in stress relief, and strengthening the body and mind is highlighted. The author focuses on how athletes can improve their health and recover from illnesses through yoga practice. The article emphasizes that it is a powerful tool for determining the quality of life for physical athletes, as well as for fat. At the same time, the article also offers practical recommendations for transferring yoga techniques to achieve high goals in sports and maintain internal purification.